Persepsi Masyarakat Terhadap Revitalisasi Alun-Alun Kota Semarang Sebagai Ruang Terbuka Publik - Mazaya Ghaizani Nadiantika; Hadi Wahyono (Jurusan Perencanaan Wilayah dan Kota, 2022)
The square is known as a landmark for a city. The square also functions as a place for people to socialize and do activities both individually and in groups. Semarang City Square underwent a change in land use in 1969 to become a trading area and losing its function as a public open space. In 2015 after the burning of Johar Market, the Semarang City Government is carrying out a revitalization project to restore Semarang City Square to its original state. Revitalization is an effort to increase the value of land through rebuilding in an area that can improve the function of the previous area. The purpose of this research is to examine the public perception of the revitalization of Semarang City Square as a public open space. The method used in this research is a qualitative method with the analysis technique of presenting data in the form of descriptive. In exploring people's perceptions, it uses aspects of community comfort when doing activities in public spaces, namely comfort, activity, accessibility, and sociability. Based on the findings, Semarang City Square before it became a trading area and after revitalization had fundamental differences in the provision of physical facilities to support the comfort of the community when doing activities in the square. The revitalization of Semarang City Square has a positive impact on society. Apart from being able to restore the cultural heritage that has been lost, the government has also succeeded in restoring the function of the Semarang City Square as a public open space.